Antibacterial activity of green synthesized silver nanoparticles using Pistacia hull against multidrug-resistant clinical isolates - Zary Nokhodian; Mohammad Mousavi-Khattat; Shima Gharibi; Soodabeh Rostami; Parisa Zeraati; Mehdi Rahimmalek; Antoni Szumny (Nanomedicine Journal, 2024)
Objective(s): Silver nanoparticles (AgNPs) can be considered as the new antibacterial agents. The antibacterial effects of synthesized AgNPs from Iranian pistachio hulls on several antibiotic-resistant bacteria were assessed in this study. Materials and Methods: In an experimental study, AgNPs were synthesized by reducing Ag+ ions using pistachio hulls. Several methods characterized the qualities of AgNPs. Antibacterial activities of the AgNPs against six gram-positive and gram-negative standard bacteria and 30 multidrug-resistant (MDR) clinical isolates were investigated by well diffusion, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) methods. Results: The aqueous extract of pistachio hulls had an acceptable potential to synthesize AgNPs, and the formed nanoparticles displayed suitable size and acceptable stability in solutions. Antibacterial activities of the AgNPs were detected against two standard strains, Escherichia coli, and Staphylococcus aureus, with growth inhibition zones of 13 and 11 mm, respectively. MIC were 10 mg/ml for E. coli and 20 mg/ml for S. aureus. MBC for both bacteria was the same as MIC. MIC and MBC AgNPs against 15 methicillin-resistant S. aureus (MRSA) isolates ranged from 40 to 10 mg/ml. In extended-spectrum beta-lactamase (ESBL) E. coli isolates, 11 and 3 isolates have MIC equal to 20 and 10 mg/ml, respectively. Three ESBL E. coli isolates had 10, 5 and 2.5 mg/ml MBC; in other isolates, MBC and MIC were the same. Conclusion: The green synthesis of AgNPs using pistachio hull can replace common chemical and physical methods. AgNPs displayed antibacterial activities, and they could replace some antibiotics.